Effect of progesterone on Candida albicans vaginal pathogenicity - Alves, Carlos (2014)
Candida albicans is responsible for the majority of cases of vulvovaginal candidosis (VVC), an infection which occurs mainly during the luteal phase of the menstrual cycle or during the pregnancy, when levels of progesterone are elevated. One of the most important candidal virulence factors is the ability to adhere to host surfaces and form biofilms. The aim of this study was to determine the influence of progesterone on C. albicans virulence, namely biofilm formation and colonisation/invasion of a reconstituted human vaginal epithelium (RHVE). Biofilm formation on the RHVE was evaluated by enumeration of culturable cells, total mass quantification and scanning electron microscopy. The capacity of C. albicans strains to invade and colonise the tissue was examined by fluorescence microscopy using species‐specific peptide nucleic acid (PNA) probe hybridisation, and quantitatively evaluated by RT‐PCR Candida quantification methodology. Furthermore, gene (BCR1 and HWP1) expression of biofilm and RHVE colonising cells was evaluated by quantitative RT‐PCR. Results confirmed that progesterone reduced the capacity of C. albicans strains to form biofilms and to colonise and invade RHVE. Additionally, it was demonstrated that progesterone decreased expression of BCR1 and HWP1, which are important virulence determinants of C. albicans. In conclusion, it was evident that progesterone can have a major influence on C. albicans pathogenicity on vaginal epithelial cells and may partly explain susceptibility of women to VVC at different stages of the menstrual cycle.